Effect of sport-related concussion on clinically measured simple reaction time. Issue 2 (11th January 2013) - Eckner, James T; Kutcher, Jeffrey S; Broglio, Steven P; Richardson, James K
Abstract : Background: Reaction time (RT) is a valuable component of the sport concussion assessment battery. RT is typically measured using computers running specialised software, which limits its applicability in some athletic settings and populations. To address this, we developed a simple clinical test of RT (RTclin ) that involves grasping a falling measuring stick. Purpose: To determine the effect of concussion on RTclin and its sensitivity and specificity for concussion. Materials and methods: Concussed athletes (n=28) and non-concussed control team-mates (n=28) completed RTclin assessments at baseline and within 48 h of injury. Repeated measures analysis of variance compared mean baseline and follow-up RTclin values between groups. Sensitivity and specificity were calculated over a range of reliable change confidence levels. Results: RTclin differed significantly between groups (p<0.001): there was significant prolongation from baseline to postinjury in the concussed group (p=0.003), with a trend towards improvement in the control group (p=0.058). Sensitivity and specificity were maximised when a critical change value of 0 ms was applied (ie, any increase in RTclin from baseline was interpreted as abnormal), which corresponded to a sensitivity of 75%, specificity of 68% and a 65% reliable change confidence level. Conclusions: RTclin appears sensitive to the effects of concussion and distinguished concussed and non-concussed athletes with similar sensitivity and specificity to other commonly used concussion assessment tools. Given its simplicity, low cost and minimal time requirement, RTclin should be considered a viable component of the sports medicine provider's multifaceted concussion assessment battery.